2018
DOI: 10.1101/496968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intake of red and processed meat, use of non-steroid anti-inflammatory drugs, genetic variants and risk of colorectal cancer; a prospective study of the Danish “Diet, Cancer and Health” cohort

Abstract: 247/300)Red and processed meat have been associated with increased risk of colorectal cancer (CRC), whereas long-term use of non-steroid anti-inflammatory drugs (NSAIDs) may reduce the risk. The aim was to investigate potential interactions between meat intake, NSAID use, and gene variants in fatty acid metabolism and NSAID pathways in relation to the risk of CRC. A nested case-cohort study of 1038 CRC cases and 1857 randomly selected participants from the Danish prospective "Diet, Cancer and Health" study enc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In the same year, Shah et al [8] showed that the cancer-related rs6983267 SNP and its corresponding CCAT2 promoted myeloid cancers through certain SNP-specific RNA gene mutations. In 2019, Andersen et al [84] highlighted that the CCAT2 rs6983267 GG genotype was correlated with an elevated CRC risk, which was in agreement with the results of previous studies. In 2021, Yu et al [85] found that the rs6983267 G allele is related to a greater risk of lung cancer than the T allele.…”
Section: Ccat2 Snps and Cancersupporting
confidence: 78%
“…In the same year, Shah et al [8] showed that the cancer-related rs6983267 SNP and its corresponding CCAT2 promoted myeloid cancers through certain SNP-specific RNA gene mutations. In 2019, Andersen et al [84] highlighted that the CCAT2 rs6983267 GG genotype was correlated with an elevated CRC risk, which was in agreement with the results of previous studies. In 2021, Yu et al [85] found that the rs6983267 G allele is related to a greater risk of lung cancer than the T allele.…”
Section: Ccat2 Snps and Cancersupporting
confidence: 78%
“…Thirdly, the prospective study design with the collection of dietary and lifestyle factors before diagnosis eliminates the risk of recall bias. A fourth advantage is diverse and high intake of meat and fibre in the cohort enabled investigations of the effects of diet and therefore the prospective “Diet, Cancer and Health” cohort has been proven suitable to detect effects of meat and fibre intake 61 - 64 . A fifth strength of this study is the consideration that individuals diagnosed with CID within 0.5, 1, and 5 years after filling out the questionnaire may have biased the results if they had systematically different exposure levels than the other late-onset CID cases.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several large-scale cohort studies that showed association between the intakes of HAAs (e.g., PhIP and MeIQx) and higher cancer risk revealed that red meat consumption largely contributed to the above positive associations (Gibis, 2016). Athough the causality between meat consumption and cancer risk is difficult to clarify, dietary intake information obtained from questionnaires and epidemiological investigations links high dietary red meat and processed meat consumption with a higher risk of human cancers, including breast cancer (Farvid et al, 2018), colorectal cancer (Wang et al, 2015), and gastric cancer (Andersen, Halekoh, Tjønneland, Vogel, & Kopp, 2019). Other studies highlighted that consumption of processed meat (50 g/day) increased the probability of some cancers, such as prostate by 4%, 18% for colonic, 9% for breast, and 19% for pancreatic (Wolk, 2017).…”
Section: Toxicology Of Heterocyclic Aromatic Aminesmentioning
confidence: 99%